2021
DOI: 10.1111/jcmm.16745
|View full text |Cite
|
Sign up to set email alerts
|

TNF‐α induces up‐regulation of MicroRNA‐27a via the P38 signalling pathway, which inhibits intervertebral disc degeneration by targeting FSTL1

Abstract: The mechanism of intervertebral disc degeneration is still unclear, and there are no effective therapeutic strategies for treating this condition. miRNAs are naturally occurring macromolecules in the human body and have many biological functions. Therefore, we hope to elucidate whether miRNAs are associated with intervertebral disc degeneration and the underlying mechanisms involved. In our study, differentially expressed miRNAs were predicted by the GEO database and then confirmed by qPCR and in situ hybridiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The most enriched biological process was Response to oxidative stress, cellular component was Cytoplasm, and molecular function was Identical protein binding. More importantly, we also investigated the potential signaling pathways involved in the repair process of NPCs cocultured with MSCs, and some of these signaling pathways have been proved to play important roles in the pathophysiology of IDD [38][39][40][41][42]. TNF signaling pathway and IL-17 signaling pathway both were inflammation-related pathways, which indicated that MSCs might reduce the oxidative stress, and then improve the inflammatory status of degenerative NPCs [38,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most enriched biological process was Response to oxidative stress, cellular component was Cytoplasm, and molecular function was Identical protein binding. More importantly, we also investigated the potential signaling pathways involved in the repair process of NPCs cocultured with MSCs, and some of these signaling pathways have been proved to play important roles in the pathophysiology of IDD [38][39][40][41][42]. TNF signaling pathway and IL-17 signaling pathway both were inflammation-related pathways, which indicated that MSCs might reduce the oxidative stress, and then improve the inflammatory status of degenerative NPCs [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, we also investigated the potential signaling pathways involved in the repair process of NPCs cocultured with MSCs, and some of these signaling pathways have been proved to play important roles in the pathophysiology of IDD [38][39][40][41][42]. TNF signaling pathway and IL-17 signaling pathway both were inflammation-related pathways, which indicated that MSCs might reduce the oxidative stress, and then improve the inflammatory status of degenerative NPCs [38,39]. MAPK signaling pathway was another vital biolog-ical pathway in the development of IDD [40][41][42] 7 Stem Cells International degenerative NPCs cocultured with MSCs.…”
Section: Discussionmentioning
confidence: 99%
“… 85 In IDD, the differentially expressed ncRNAs are involved in regulating cell apoptosis and proliferation, ECM degeneration and inflammation. miR‐338‐3p, 86 miR‐27a 87 and miR‐133a‐5p 88 are upregulated in IDD tissues, and target SIRT6, FSTL1 and FBXO6, respectively, participating in regulating NP cell apoptosis, proliferation and ECM synthesis. The downregulated miR‐181a, 89 miR‐623 90 and miR‐874‐3p 91 are related to inflammatory response and ECM degradation.…”
Section: Nc Rnamentioning
confidence: 99%
“…By studying three common human cancers ( Zhang et al, 2021b ), namely, colon cancer, esophagus cancer, and kidney cancer, many miRNAs were confirmed to be connected with the three kinds of cancer. In addition, many studies have proven that miRNA is related to the pathological processes of intervertebral disc degeneration ( Shi et al, 2021b ), muscle atrophy ( Zhang et al, 2021a ), and cardiovascular diseases ( Liu et al, 2021a ).…”
Section: Mirnas and Oamentioning
confidence: 99%